The situation of Turkish immigrants in Germany after unification (1990 _ 1997): Historical Study - Ahmed, Rezan Jalal (Al-Adab Journal, 2021)
The collapse of The Berlin Wall on 9rd- November – 1989,an important milestone in ending the Fragmentation and declaring German unity on 3rd of October 1990, the beginning of new phase for the stability of Turkish immigrants, Continuing and claiming German Citizenship continues, and the committed the German government to that .